A Sociedade Paraense de Defesa dos Direitos Humanos e o Serviço Nacional de Informações: vigilância e a construção do inimigo interno durante a Ditadura Militar brasileira (Revista de História Regional, 2026)
Abstract: The article analyzes the systematic surveillance imposed on the Sociedade Paraense de Defesa dos Direitos Humanos (SDDH) by the Serviço Nacional de Informações (SNI) during the Military Dictatorship (1964–1985). Founded in Belém, Pará, in August 1977, the SDDH was motivated by the defense of squatters involved in the Fazenda Capaz conflict. The entity used its mouthpiece, the newspaper Resistência, to denounce state violence and the capitalist and authoritarian logic governing the occupation of the Amazon. Its “Carta de Princípios” (Charter of Principles) listed core objectives such as the struggle for housing, land access, and democratic guarantees. The SNI documentation, consulted after the archives were released, shows that the SDDH was quickly framed within the logic of the “internal enemy”. State agents associated the fight for rights with “subversion,” “disorder,” and an “anti-revolutionary spirit”, labeling the entity’s actions, such as raising social justice issues, as “ferment for the class struggle”. The monitoring was sophisticated, with the first systematic SNI record dating to September 1977, just weeks after the SDDH’s founding. Detailed reports described meetings, action plans, and member profiles, such as President Paulo Fonteles. Fonteles' case illustrates the clash of narratives: while official documents branded him as an "element with subversive background", Resistência published his testimony of torture and systematic violence, emphasizing that repression persisted in the Amazon even during the regime’s announced “opening”.
Keywords: Sociedade Paraense de Defesa dos Direitos Humanos (SDDH); Military Dictatorship; Serviço Nacional de Informações (SNI); Amazon; state of Pará.